Strategic Management and Waqf : A Proposition - Tiara Puspa (Indonesian Management and Accounting Research, 2018)
These studies build  proposition about waqf  as become one competitive advantage  issue which develops under  a model of management strategy.  Although there was three step in  that model, these study only discuss  the first step which is formulation strategy to determine external factors that considerate opportunity and threats.    A lot of threats  comes from  the situation like   the habit to give priority into physical needs, ages such as biographical characteristics, investor mindset, government policy,   and globalization could be factors that hinder people from doing waqf. Beside that nazir attitude and behavior explained  strength and weakness managing waqf.  Although  these study  only describes the proposition, as a basic idea to do next research, but its gives a contribution  on  how to  proof  factors that shape  threats and opportunity to   formulate a strategy implement waqf  successfully. Key  Words : Strategy, Waqf, Opportunity, Threats, Strength, Opportunity